Impact, benefits, security, and privacy of fintech adoption in Indonesia: A literature review - Verni Juita; Husna Roza; Rita Rahayu (Operations Management and Information System Studies, 2022)
The growth of Financial Technology (FinTech) in Indonesia has continued to increase in recent years, along with the development of information technology and the use of the internet. These developments have driven the rapid growth of studies related to Fintech in Indonesia. In this regard, this research intends to conduct a systematic literature review of various studies related to FinTech in Indonesia that were made and published in the last ten years. To achieve this objective, this study utilizes the publish and perish application version 7 to access the Google Scholar database and select it using several keywords that match this research topic. The reviewed studies were selected based on the level of accreditation of the journal where the research articles were published, either by national accreditation (Sinta) or international accreditation (Scopus). Furthermore, they were analyzed and processed using simple descriptive statistical analysis using MS Excel. This research found that over the past ten years, there are 79 journal articles related to Fintech in Indonesia, of which 44 of them are published in journals accredited by Sinta, and the rest 35 were accredited by Scopus. Moreover, most of the reviewed studies only discuss the usage of Fintech in general, especially those related to the use of P2P Lending and mobile payments. Regarding the methodology used in the studies, there are significant differences between journal articles published in the Scopus and Sinta Journals. The Scopus-accredited journal articles are dominated by research using quantitative methods, whereas the Sinta-accredited journal articles tend to use qualitative methods. These results highlight that there is still plenty of room to extend the research topic of fintech studies in Indonesia, such as the security and privacy issues related to fintech adoption.